L’approche métamorphique de l’éducation : l’éducation comme souci de soi - Alfred Romuald Gambou (Recherches en Éducation)
The old Greco-Roman tradition has ontologically conceived about human position in the relation subject-truth, this is also one of the main characteristics of its educational paradigm. Indeed, if the interpretation of this relationship was the understanding of care for the self concept, it has also structured different philosophical schools orientation including those from Socrates and Zeno of Citium, while giving each one its version in its interpretative pattern. The problem is that modernity does not hesitate to break with the ontological structure, which was his “spirituality”. Thus defined, a break in this relationship subject-truth did not fail consequences in the context of modern formation of man. The aim of this research is not only to understand the operation of each school pattern mentioned before but also to understand their ramifications in history, thereby to question the relevance of our contemporary education, self transformation and teaching professional ethics.